PENGARUH MEDIA SOSIAL TERHADAP KESEHATAN MENTAL MAHASISWA (Studi Kasus di Perguruan Tinggi Keagamaan Katolik Regio Timor Provinsi Nusa Tenggara Timur) - Dau, Yoseph Lodowik Deki; Bele, Graciana Amanda (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2024)
This study aims to explore the relationship between social media and mental health of students in two pastoral colleges in Timor Region. The results of descriptive analysis showed that the majority of students (69.81%) actively use social media, while most of them (69.88%) have a good level of mental health. Inferential analysis showed a t-value of 3.307 with a significance level of 0.001, which is significantly lower than the general threshold of 0.05. This indicates that there is strong evidence that social media use has a positive and significant effect on the mental health of students in both pastoral colleges. Recommendations from this study include efforts to improve understanding of the risks and benefits of social media use through targeted education. In addition, it is recommended to develop a policy on responsible social media use in the academic environment. Counseling support and resources related to mental health also need to be improved to provide more effective assistance to students in managing their mental health. This study makes an important contribution to expanding the understanding of the impact of social media on mental health in the context of pastoral higher education. The practical implications of these findings are expected to assist educational institutions in developing more holistic strategies to support overall student well-being.